2017
DOI: 10.1002/tea.21392
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and research at a large university: Case studies of science professors

Abstract: Current STEM workforce issues and retention problems faced by postsecondary STEM education have renewed research efforts in this arena. A review of literature on STEM professors indicates that although this population reports difficulties integrating teaching and research responsibilities, there have not yet been any qualitative studies conducted to deeply investigate the complexities of managing teaching, research, and service. This work utilized a set of four phenomenological case studies conducted over a 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
(57 reference statements)
4
19
0
Order By: Relevance
“…We also found that FIBIS was able to identify how STEM faculty internal characteristics (e.g., teaching identity, beliefs) played an important role in implementation of EBIPs at different levels of effort. These findings from FIIBS aligns with prior research suggesting that faculty background and beliefs coming into the university plays a key role in how resistant faculty are to implementing EBIPs (White, 2016;Robert & Carlsen, 2017;Oleson & Hora, 2014). Further, when asked what faculty were dissatisfied with in their teaching using EBIPs, internal influences relating to beliefs, confidence, and knowledge were reported most often for faculty in this pilot study.…”
Section: Ebips Barriers and Identitysupporting
confidence: 85%
See 2 more Smart Citations
“…We also found that FIBIS was able to identify how STEM faculty internal characteristics (e.g., teaching identity, beliefs) played an important role in implementation of EBIPs at different levels of effort. These findings from FIIBS aligns with prior research suggesting that faculty background and beliefs coming into the university plays a key role in how resistant faculty are to implementing EBIPs (White, 2016;Robert & Carlsen, 2017;Oleson & Hora, 2014). Further, when asked what faculty were dissatisfied with in their teaching using EBIPs, internal influences relating to beliefs, confidence, and knowledge were reported most often for faculty in this pilot study.…”
Section: Ebips Barriers and Identitysupporting
confidence: 85%
“…Faculty, particularly those at researchintensive universities, can identify with both the teacher/ educator profession and the research profession. However, many times, these identities can be in tension, which may be due to the institutional and individual value placed on these two responsibilities (e.g., Brownell & Tanner, 2012;Fairweather, 2008;Robert & Carlsen, 2017).…”
Section: Professional Identitymentioning
confidence: 99%
See 1 more Smart Citation
“…Institutional pressures surrounding a faculty position set the incentives for faculty ( Henderson and Dancy, 2007 ). This means that faculty must learn how to appropriately balance time and effort between research and pedagogy to meet the expectations for tenure and promotion in their departments, as well as at the university level ( Hardré et al , 2010 ; Savkar and Lokere, 2010 ; Robert and Carlsen, 2017 ). Departments may provide guidelines for faculty—such as 40% research, 40% teaching—but such ratios are abstract administrative expectations and usually not tied to how much time faculty will need to spend on research to meet tenure standards.…”
Section: A Cultural Evolutionary Model Of Pedagogymentioning
confidence: 99%
“…Departments may provide guidelines for faculty—such as 40% research, 40% teaching—but such ratios are abstract administrative expectations and usually not tied to how much time faculty will need to spend on research to meet tenure standards. While some research suggests that extrinsic institutional incentives drive faculty to emphasize their focus on research ( Leslie, 2002 ; Light et al , 2009 ; Anderson et al , 2011 ; Bradforth et al , 2015 ), other evidence suggests that faculty may be more motivated by intrinsic motivations ( Robert and Carlsen, 2017 ; Shortlidge et al , 2017 ). During the pre-tenure phase, academics at research-focused institutions are further incentivized to continue prioritizing research and grants.…”
Section: A Cultural Evolutionary Model Of Pedagogymentioning
confidence: 99%